A dose ranging phase I/II trial of the von Willebrand factor inhibiting aptamer ARC1779 in patients with congenital thrombotic thrombo - cytopenic purpura - Jilma-Stohlawetz, Petra; Gilbert, James C.; Gorczyca, Monika E.; Knöbl, Paul; Jilma, Bernd (Thrombosis and Haemostasis, 2011)
Congenital thrombotic thrombocytopenic purpura (TTP) is a very rare but potentially life-threatening disorder. This phase I/II trial compared the pharmacokinetics and pharmacodynamics and safety of three different administration modes of the anti-von Willebrand factor (VWF) aptamer ARC1779. This was a prospective clinical trial with a partial cross-over design: three periods comprised subcutaneous injections of 50 mg of ARC1779 on seven subsequent days, a low-dose infusion of ARC1779 (0.002 mg/kg/min) for 24–72 hours and a high-dose infusion (0.004–0.006 mg/kg/min) up to 72 hours. ARC1779 concentrations were determined with high performance liquid chromatography, VWF inhibition was measured with enzyme immunoassay and platelet function was determined with the platelet function analyser (PFA-100) and impedance aggregometry. ARC1779 was well tolerated without any bleeding at concentrations spanning over three orders of magnitude. The daily s.c. injection yielded plasma levels (0.5 μg/ml) of the drug that were too low to sufficiently suppress VWF. The low-dose i.v. infusion increased platelet counts in one patient, whereas the high i.v. dose increased plasma concentrations up to 69 μg/ml, completely blocked free A1 domains, VWF-dependent platelet plug formation and enhanced platelet counts in 2/3 patients. In conclusion, infusion of ARC1779 dosedependently inhibits VWF-dependent platelet function and during infusion ARC1779 increases or stabilises platelet counts in congenital TTP. However, the tested doses, particularly the daily s.c. injections, did not correct all clinical or laboratory features of TTP.
Keywords: Clinical trial; ARC1779; aptamer; von Willebrand factor; congenital thrombotic thrombocytopenic purpura; Upshaw-Schulman syndrome